Evidence for the decays B0 → D(∗)0ϕ and updated measurements of the branching fractions of the B0s → D(∗)0ϕ decays - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; et al. (Journal of high energy physics, 2023)
Evidence for the decays B0 → D0ϕ and B0 → D∗0ϕ is reported with a significance of 3.6 σ and 4.3 σ, respectively. The analysis employs pp collision data at centre-of-mass energies √s = 7, 8 and 13 TeV collected by the LHCb detector and corresponding to an integrated luminosity of 9 fb−1. In these results, the first uncertainty is statistical, the second systematic, and the third is related to the branching fraction of the B0 → D0K+K− decay, used for normalisation. By combining the branching fractions of the decays B0 → D(∗)0ϕ and B0 → D(∗)0ω, the ω-ϕ mixing angle δ is constrained to be tan2 δ = (3.6 ± 0.7 ± 0.4) × 10−3, where the first uncertainty is statistical and the second systematic. An updated measurement of the branching fractions of the B0 s → D(∗)0ϕ decays, which can be used to determine the CKM angle γ.